Description of four new species of the Neotropical genus Scione Walker, 1850 (Diptera: Tabanidae) - Oliveira, Lia Pereira; Henriques, Augusto Loureiro; Buestán, Jaime; Krolow, Tiago Kütter (European Journal of Taxonomy, 2024)
After 94 years after the last revision of the genus and after 22 years since the last species was named, we describe four new species of Scione from Ecuador and Peru: S. cooperi sp. nov., S. gertrudeae sp. nov., S. kroeberi sp. nov. and S. merianae sp. nov. We provide diagnoses, descriptions, photographs and discussions for each of the species.